Multilevel modeling analysis of bottle feeding and its determinants among children 0-23 months in East Africa: evidence from recent DHS data (2015-2022) - Bewuketu Terefe; Adane Habtie; Bogale Chekole (BMC, 2024)
Abstract Background Despite breastfeeding recommendations, the prevalence and length of breast milk feeding in developing nations is rapidly decreasing, with bottle feeding taking its place. This reduces the effectiveness of breastfeeding and is associated with diarrheal disease mortality and morbidity. The purpose of this study was to determine the prevalence, distribution, and determinants of bottle feeding among under-two-year-old children in the region. Methods The ten East African countries' Demographic and Health Surveys (DHS) recent data from 2015 to 2022 was used. The data were weighted using sample weights for probability sampling and nonresponse. The study used 43,150 weighted children. A multi-level logistic regression model was used, and P - values of ≤ 0.2 and < 0.05 were used to declare candidate variables in the binary, and multivariable to declare significant variables, respectively. Results The prevalence of bottle feeding among children under-two-years-old in East Africa was 10.08% (95% CI 9.79, 10.36), ranging from 4.04% (95% CI 3.56, 4.53) in Tanzania to 33.40% (95% CI 32.72, 34.08) in Kenya. High antenatal care communities (AOR 1.22; 95% CI 1.11, 1.35), mothers aged 25-34 years (AOR 1.17; 95% CI 1.06, 1.28), high wealth index communities (AOR 1.12; 95% CI 1.02,1.25), women who had at least one types mass media exposure (AOR 1.64; 95% CI 1.53, 1.77), women from communities with high level mass media exposure (AOR 1.36; 95% CI 1.23, 1.52), given first birth after teenage years (AOR 1.17; 95% CI 1.09, 1.26), having more than one health visit in the year (AOR 1.37; 95% CI 1.27,1.47), multiple children (AOR 1.46; 95% CI 1.22, 1.75) were associated with higher rates of bottle feeding. Whereas a primary education (AOR 0.51; 95% CI 0.47, 0.54), having 3-5 living children (AOR 0.86; 95% CI 0.79, 0.95), a rural setting (AOR 0.53; 95% CI 0.49, 0.58), and a long distance from health facilities (AOR 0.84; 95% CI, 0.78, 0.91) were associated with lower rates of bottle feeding. Conclusions The overall prevalence of bottle feeding was moderate in East African countries. Improving the availability and accessibility of health facilities to mothers, utilizing maternal healthcare, and media exposure will contribute to a significant decrease in the inappropriate bottle feeding of children in East Africa.